Combining ability and genetic divergence to select testers to grain yield and forage potencial - Costa Rosa, Jocimar; Faria, Marcos; Zaluski, Welton; Uhdre, Renan; Andreoli, Pedro; Sagae, Vitor (Revista Ciência Agronômica, 2021)
Genetic distance analysis among testers and lineages and the correlation of genetic distance with combining ability can be an important alternative to select maize genotyps to grain yield and forage potential since testers dedicated to both purposes are rare. The objective of this work was to select testers for grain yield and forage traits based on the association between genetic divergence, general combining ability and genetic parameters in topcrosses. The experiments were conducted in the 2015/16 and 2016/17 crop harvests. 150 topcrosses were evaluated among 30 S4 maize progenies and testers AG8025, P30B39, MLP102, 60.H23.1 and 70.H26.1. The evaluated traits were plant height, ear height, grain yield, dry mass yield, neutral detergent fiber and acid detergent fiber and forage in situ digestibility. There was not a single suitable tester for grain yield and forage traits. The 70.H26.1 tester is the most recommended for grain yield. The 60.H23.1 tester is the most recommended for forage traits. There was not linear correlation between genetic divergence, general combining ability and genetic parameters.